A fine resolution CDF simulation approach for biomass cook stove development - Miller-Lionberg, Daniel David, author; Willson, Bryan, advisor; DeFoort, Morgan, committee member; Sakurai, Hiroshi, committee member; Volckens, John, committee member (Colorado State University. Libraries, 2011)
More than half of the world's population meets cooking and heating needs through small-scale biomass combustion. Emissions from these combustion processes are a major health hazard and air pollution concern. Simple improvements over traditional cooking fires have been shown to increase combustion and heat transfer efficiency while reducing physically harmful gaseous and particulate matter (PM) emissions. Over approximately 30 years of modern stove development history, designs have largely been based on empirical guidelines, and attempts at improvements have been made through an iterative, trial-and-error approach. Feedback in this design process is typically attained through bulk measurements made during experimental testing of prototypes. While important for assessing the performance of a stove, such testing offers no information on the fine spatial or temporal scales of phenomena within the stove, leaving it a "black box" in the view of the designer. Without higher resolution information, the rate and ultimate level of design improvement may be limited. In response, a computational fluid dynamic (CFD) simulation of a common, production cook stove is conducted using ANSYS FLUENT 13.0 software. Aspects critical to achieving high spatial and temporal resolution flow and temperature field results are included, enabled by necessary simplifications to less important elements. A model for the steady, time-averaged drying and pyrolysis of wood stick fuel is used in conjunction with a consideration for the simultaneous oxidation of the resulting char, to generate gas-phase fuel boundary conditions for the simulation. Fine spatial and temporal resolution are simultaneously possible in an unsteady formulation with the use of the simplified fuel condition, reduced-mass solid boundaries, and abbreviated runtimes. Employment of a large eddy simulation (LES) turbulence model is proposed as necessary to realistically consider the larger scales of gas mixing. Combustion heat release is approximated by reactions dictated by a mixture fraction formulation, assuming equilibrium conditions in a non-adiabatic system, affected by turbulent fluctuations through a probability density function (PDF). Sensitivity studies are conducted on grid parameters, boundary condition assumptions, and the duration of simulation runtime necessary to achieve result significance. A model for particulate emission formation is secondarily explored. A thermocouple-instrumented stove is used in an experiment to generate internal gas temperature profiles for the validation of the CFD simulation through comparable results. Likewise, a heat-exchanger integrated into a cooking pot is employed with the instrumented stove to measure short time-scale heat transfer values that are compared to the CFD simulation results, as well as to benchmark test data from the production stove. Recommendations for future efforts in stove simulation are made.
Keywords: CFD; combustion; cookstoves; cook stoves; pyrolysis; simulation